The longitudinal muscle of rat ileum as a sensitive monoreceptor assay for bradykinin B1 receptors. - Meini, S. (1996)
1. Various bradykinin derivatives, acting preferentially at B1 or B2 receptors, were tested in the isolated longitudinal smooth muscle of rat ileum. Experiments were carried out in the presence of chlorpheniramine and atropine (both 1 microM), guanethidine and indomethacin (both 3 microM) and of the peptidase inhibitors (captopril, bestatin and thiorphan, all 1 microM). 2. The rank order of potency was (pD2 values +/- s.e.mean, n = 5 in parentheses, at 5 h from set-up): [des-Arg9]-BK (8.27 +/- 0.11) > or = [des-Arg10]-kallidin (7.67 +/- 0.24) > bradykinin (6.69 +/- 0.25). The B2 receptor selective agonist, [Hyp3,Tyr(Me)8]-BK, was approximately 10 fold less active than bradykinin. Contractile responses to all agonists increased with time. The maximal response to the B1 receptor agonist, [desArg9]-BK at 5 h (94 +/- 2%) was significantly (P < 0.05) greater than that measured at 2 h (74 +/- 2%). 3. The B2 receptor antagonist, D-Arg[Hyp3, Thi5, D-Tic7, Oic8]-BK (Hoe 140, 0.1 microM) did not affect responses to the B1 receptor agonist [des-Arg9]-BK (0.1 nM--1 microM) nor those to the B2 receptor agonist, [Hyp3,Tyr(Me)8]-BK (1 nM--10 microM). In control experiments performed in the longitudinal smooth muscle of guinea-pig ileum and rat isolated urinary bladder as bioassays for B2 receptors, the B2 receptor antagonist Hoe 140 (0.1 microM) antagonized bradykinin-induced contractions. 4. In the rat isolated ileum the B1 receptor antagonist, D-Arg[Hyp3, Thi5, D-Tic7, Oic8, des-Arg9]-BK ([des-Arg10]-Hoe 140, 0.3 - 10 microM) competitively antagonized contractile responses to [des-Arg9]-BK with an estimated pKB of 6.74 +/- 0.08 (Schild plot slope with confidence limits 1.22, (0.70 - 1.73) n = 13). In control experiments in the guinea-pig isolated ileum and rat isolated urinary bladder, [des-Arg10]-Hoe 140 (1 - 10 microM) did not inhibit B2 receptor-mediated contractile responses. 5. The putative B1 receptor antagonist, [Leu8,des-Arg9]-BK, behaved as a partial agonist when responses were determined 2 h from set-up (pD2 6.43 +/- 0.21, n = 5; Emax 30% of that evoked by [des-Arg9]-BK); at 5 h from set-up it behaved as a full agonist (pD2 7.48 +/- 0.12, n = 5; Emax 90% of that evoked by [des-Arg9]-BK). At this time the response to [Leu8,des-Arg9]-BK was antagonized in a concentration-dependent manner by [des-Arg10]-Hoe 140, which at 1 microM and 10 microM, produced dose-ratios of 6.33 +/- 3.66 (n = 4) and 103 +/- 40 (n = 4). 6. In view of the rank order of potency of agonists, the antagonist activity by [des-Arg10]-Hoe 140 and the lack of antagonist activity of Hoe 140, we conclude that the longitudinal smooth muscle of rat ileum, after histamine, acetylcholine, noradrenaline, and prostanoid production blockade, is a sensitive monoreceptor assay for studying the pharmacology of bradykinin B1 receptors. Further the preparation can also be used as a sensitive bioassay to identify partial agonist activity of B1 receptor antagonists such as [Leu8,desArg9]-BK.